Controle de rotores flexíveis suportados por mancais magnéticos - Oliveira, Marcus Vinicius Fernandes de (2019)
The present work is devoted to the development of controllers utilized in supercritical rotors supported by magnetic bearings. The first step was the conception of a numerical/computational model in the MATLAB/SIMULINK environment, as based on the specifications provided by the test rig manufacturer. Following, this model was tested through an experimental validation process, resulting a mathematical model that represents closely the dynamic behavior of the actual physical system. Next step was the synthesis of two PID controllers, the first being a manufacturer-supplied PI controller and the second is an adaptive PID controller. Both the controllers were evaluated from their closed-loop transfer functions in the perspective of their corresponding imbalance responses, which was conducted according to API 684 guidelines and classified as based on the criteria defined in the standard ISO 14839-2. Then, it was possible to select the best performing controller for the creation of a Kriging sorrogate model, which was evaluated by using the same criteria applied to the PID and adaptive PID controllers. The results obtained permit to state that the main contribution of the present research work was the systematization of the application of Kriging surrogate model on the study and design of supercritical rotors supported by magnetic bearings.